Continuous cryotherapy vs. traditional cryotherapy after total knee arthroplasty: A systematic review and meta-analysis of randomized controlled trials - Liu, Meng-Meng; Tian, Mian; Luo, Changqi; Wang, Shicheng; Shao, Long (Frontiers in Surgery, 2023)
Background: Cryotherapy is widely applied to relieve pain and improve functional outcomes after total knee arthroplasty (TKA). New cryotherapy devices have recently been developed to guarantee a fixed temperature for a prolonged time. Therefore, we conducted a systematic review and meta-analysis to compare continuous cryotherapy and traditional cryotherapy (ice bag or gel pack) for patients after TKA. Methods: This study was conducted according to a predefined protocol registered on PROSPERO. Two independent reviewers performed an electronic database search of PubMed, Embase, Cochrane, Web of Science, Google Scholar, and ClinicalTrials.gov. Dichotomous outcomes were reported as risk difference (RD) with 95% confidence intervals (CIs), and continuous outcomes were reported as mean difference (MD), or standardized mean difference (SMD) with 95% CIs. Results: Seven trials enrolling a total of 519 patients were included. There were no differences in pain intensity (MD -0.54, 95% CI -1.55–0.47; P = 0.30), analgesics consumption (MD -0.37, 95% CI -1.28–0.55; P = 0.43), postoperative range of motion (MD 0.47, 95% CI -4.09–5.03; P = 0.84), swelling of the knee joint, blood loss, change in hemoglobin, or transfusion rate. Meanwhile, there were no differences in length of hospital stay (MD -0.77, 95% CI -1.62–0.08; P = 0.07) and adverse events (RD 0, 95% CI -0.02–0.03; P = 0.74). In addition, continuous cryotherapy leads to extra costs and resources than traditional cryotherapy. Conclusions: Continuous cryotherapy does not appear to offer significant benefits for TKA when compared with traditional cryotherapy. Based on currently available evidence, traditional cryotherapy is still recommended as continuous cryotherapy is not cost-effective. Further well-designed studies with larger sample sizes are warranted to further confirm these preliminary results. PROSPERO Registration Number: CRD42022308217